2021
DOI: 10.1111/apha.13641
|View full text |Cite
|
Sign up to set email alerts
|

Local cyclic adenosine monophosphate signalling cascades—Roles and targets in chronic kidney disease

Abstract: More than 700 million people worldwide suffer from chronic kidney disease (CKD), 1,2 and the prevalence of the disease is further increasing. In 1990, CKD was ranked 27th in the list of causes of the total number of global deaths, whereas in 2010 it was already placed 18th. 3 In 2017, CKD was the 12th leading cause of death worldwide (1.2 million deaths). 4 The epidemiological characteristics of CKD vary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 322 publications
(633 reference statements)
0
10
0
Order By: Relevance
“…102 The research by Sholokh and Klussmann reported that cAMP directs the renin release from juxtaglomerular cells and plays a role in sodium reabsorption in the kidney. 103 Increased levels of cAMP have been reported to have anti-inflammatory and tissue-protective effects. 104 Adenosine was detected in our research, and regulation of the cAMP signaling pathway may be one of the pathways for the peptide NCW action.…”
Section: Purinergic Signalingmentioning
confidence: 99%
“…102 The research by Sholokh and Klussmann reported that cAMP directs the renin release from juxtaglomerular cells and plays a role in sodium reabsorption in the kidney. 103 Increased levels of cAMP have been reported to have anti-inflammatory and tissue-protective effects. 104 Adenosine was detected in our research, and regulation of the cAMP signaling pathway may be one of the pathways for the peptide NCW action.…”
Section: Purinergic Signalingmentioning
confidence: 99%
“…Except for the CRH‐ACTH‐cortisol pathway, AVP secreted from the pituitary, which acts on the kidney, is also involved in water homeostasis by reabsorption of water in vertebrates (Boone & Deen, 2008). A great number of studies revealed that an elevation of circulating blood volume and blood pressure caused a decrease in AVP secretion, thereby inducing a decline in water reabsorption in the kidney (Zeynalov et al, 2020; Li et al, 2012; Sholokh & Klussmann, 2021). Seawater fish, due to their hypoosmolity, have to drink much sea water and reabsorb the water in the kidney (Kato et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, water homeostasis is also regulated by arginine vasopressin (AVP, also known as ADH) secreted from the pituitary (Boone & Deen, 2008). AVP is released into the circulation due to hypovolemia and/or hyperosmolarity and promotes the reabsorption of water in the kidney (Zeynalov et al, 2020; Li et al, 2012; Sholokh & Klussmann, 2021). However, FW fish secrete hypotonic urine to discharge extra water absorbed through the gill and skin (Nebel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic adenosine monophosphate (cAMP) is an important physiological active substance broadly existed in living cells. As a second messenger, cAMP has numerous regulation functions, for instance expanding blood vessels, relaxing smooth muscle, stimulating adrenaline secretion and promoting nerve regeneration (Mcphee et al 2005;Sholokh and Klussmann 2021). Owing to its signi cant functions, cAMP was extensively applied in treatment of cardio-cerebrovascular diseases and area of animal feed additive attracting extensively attentions (Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%